“Muslim ballot box barbeque”: Muslim and national identities among Nigerian and Indian immigrants in Dallas/Fort Worth, Texas after September 11 - Cordell, Dennis (Diversité urbaine)

(untitled) (Groupe de recherche diversité urbaine, 2008)
AbstractThe attacks of September 11, 2001 in New York City profoundly affected Muslims in the United States. Set against national and regional demographic profiles of the Muslim population, this article analyzes its impact on a dozen Indian and Nigerian Muslim immigrants in Dallas/Fort Worth (DFW). Interviewed in an NSF study, they expressed serious concerns about discrimination and even their physical safety after the attacks. They remain both faithful Muslims and, at the same time, loyal members of their national communities. Far from being alienated from American society at large, however, they are surprisingly optimistic about their own ability, and the ability of their fellow Indians and Nigerians, and their fellow Muslims to be part of it. Indeed, their political and social engagement in the larger society, like that of their fellow Muslims in DFW, has even intensified since September 11.